Jahresbericht Kunstsammlung Nordrhein-Westfalen Düsseldorf 93-94. - Zweite, Armin; Kunstsammlung Nordrhein-Westfalen, Düsseldorf (Düsseldorf : Kunstsammlung Nordrhein-Westfalen, 1995)
Beuys, Joseph ; Kirkeby, Per ; Andre, Carl ; Newman, Barnett ; Baertling, Olle ; Ernst, Max ; Rauschenberg, Robert ; Twombly, Cy ; Braque, Georges ; Kirchner, Ernst Ludwig ; de Chirico, Giorgio ; Bonnard, Pierre ; Aratjara ; Bissier, Julius ; Long, Richard ; etc.
boek